2011
DOI: 10.1242/dev.072587
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the adult zebrafish brain from neurogenic radial glia-type progenitors

Abstract: SUMMARYSevere traumatic injury to the adult mammalian CNS leads to life-long loss of function. By contrast, several non-mammalian vertebrate species, including adult zebrafish, have a remarkable ability to regenerate injured organs, including the CNS. However, the cellular and molecular mechanisms that enable or prevent CNS regeneration are largely unknown. To study brain regeneration mechanisms in adult zebrafish, we developed a traumatic lesion assay, analyzed cellular reactions to injury and show that adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
514
3
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 406 publications
(553 citation statements)
references
References 85 publications
34
514
3
2
Order By: Relevance
“…Immunohistochemistry on cryosections was performed as previously described 51 . Briefly, to retrieve the antigens of Prox1, sections were pre-incubated in 50 mM Tris-buffer (pH 8.0) at 99°C for 5 minutes, cooled down to RT over 15 minutes and washed for 5 minutes in PBS and twice for 10 minutes in PBSTx.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry on cryosections was performed as previously described 51 . Briefly, to retrieve the antigens of Prox1, sections were pre-incubated in 50 mM Tris-buffer (pH 8.0) at 99°C for 5 minutes, cooled down to RT over 15 minutes and washed for 5 minutes in PBS and twice for 10 minutes in PBSTx.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, investigating the molecular basis of the regenerative aptitude of zebrafish brain is an interesting realm of research that might explain the fundamental difference how fish and mammalian brains react after an injury, and also endow avenues for regenerative medical therapies in humans. In order to understand the molecular infrastructure of vertebrate brain plasticity and regeneration, glial cells serve as an important research area as they are the neurogenic progenitors 3,8,20 . Thus, using CVMI technique to alter gene function in the radial glial cells of the zebrafish brain is instrumental in elucidating how fish brain can couple progenitor activity to efficient adult neurogenesis and regenerative response.…”
Section: Discussionmentioning
confidence: 99%
“…Several stem cells zones of the adult zebrafish brain have been analyzed and it has been shown that the cells lining the ventricular surface of those regions serve as progenitor cells 9,[11][12][13][14][15][16][17][18][19][20] . Detailed analyses in the zebrafish telencephalon, for example, identified the radial glial cells, which delineate the ventricular surface of this brain region to be neurogenic progenitors 19,20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regenerative capacities are not only conserved between lower vertebrates and mammals in terms of signalling. It is worth noting that both neurogenic adult neural progenitors in fish and mammals have a similar morphological phenotype and niche-they all appear to be derived from ventricular radial glia [15,16].…”
Section: Rising From the Ashes Of The Deadmentioning
confidence: 99%